Physical characterization of the deep-space debris WT1190F: A testbed for advanced SSA techniques. Issue 1 (1st January 2019) - Buzzoni, Alberto; Altavilla, Giuseppe; Fan, Siwei; Frueh, Carolin; Foppiani, Italo; Micheli, Marco; Nomen, Jaime; Sánchez-Ortiz, Noelia
Abstract: We report on extensive BVR c I c photometry and low-resolution ( λ / Δ λ ∼ 250 ) spectroscopy of the deep-space debris WT1190F, which impacted Earth offshore from Sri Lanka, on 2015 November 13. In spite of its likely artificial origin (as a relic of some past lunar mission), the case offered important points of discussion for its suggestive connection with the envisaged scenario for a (potentially far more dangerous) natural impactor, like an asteroid or a comet. Our observations indicate for WT1190F an absolute magnitude R c = 32.45 ± 0.31, with a flat dependence of reflectance on the phase angle, such as dR c / d ϕ ∼ 0.007 ± 2  mag deg −1 . The detected short-timescale variability suggests that the body was likely spinning with a period twice the nominal figure of P flash = 1.4547 ± 0.0005 s, as from the observed lightcurve. In the BVR c I c color domain, WT1190F closely resembled the Planck deep-space probe. This match, together with a depressed reflectance around 4000 and 8500 Å may be suggestive of a "grey" (aluminized) surface texture. The spinning pattern remained in place also along the object fiery entry in the atmosphere, a feature that may have partly shielded the body along its fireball phase perhaps leading a large fraction of its mass to survive intact, now lying underwater along a tight ( ∼ 1 × 80  km) strip of sea, at a depth of 1500 m or less. Under the assumption of Lambertian scatter, an inferred size of 216 ± 30 / α / 0.1  cm is obtained for WT1190F. By accounting for non-gravitational dynamical perturbations, the Area-to-Mass ratio of the body was in the range ( 0.006 ⩽ AMR ⩽ 0.011 )  m 2  kg −1 . Both these figures resulted compatible with the two prevailing candidates to WT1190F's identity, namely the Athena II Trans-Lunar Injection Stage of the Lunar Prospector mission, and the ascent stage of the Apollo 10 lunar module, callsign "Snoopy". Both candidates have been analyzed in some detail here through accurate 3D CAD design mockup modelling and BRDF reflectance rendering to derive the inherent photometric properties to be compared with the observations.